Mengenal Masjid Nahdliyin dalam Peranan Masjid Jami Kajen - Novita Siswayanti (Direktorat Jenderal Bimbingan Masyarakat Islam, 2018)
Knowing the Nadhliyin Masjid can be known from the role of Jami Kajen Masjid. Jami Kajen Masjid one of the genealogy Islamic spread and growth of Nahdliyin Boarding School Kajen Pati in maintaining religion cultural identity. This article uses qualitative research methods by describing the religious amaliah in Jami Kajen Masjid then analyzed and interpreted. In this study found the role of Jami Kajen Masjid as the Nahdliyin Masjid: first, as a place of worship shalawat, zikir together and shake hands finished prayer; second, prayer together like istigasah, tahlilan, yasinan, khataman Al-Quran and shalawat barzanji; third, the study of the religious sciences; the fourth, preserving the Arabic-speaking Friday sermons, tarawih prayers for two groups and reading Al Qur’an; the fifth, social activities providing compensation to the poor, dhuafa and orphans; the sixth, the harmony place and ukhuwah islamiyah; the seventh, the Center for Cultural Conservation traditions of megengan and suronan; eighth, the salvation tradition or celebrating the days of Islam and suronan Kiai Ahmad Mutamakin. Mengenal Masjid Nadhliyin dapat diketahui dari peranan Masjid Jami Kajen sebagai salah satu genealogi penyebaran Islam dan pertumbuhan pesantren bernuansa Nahdliyin di Kajen Pati dalam memelihara identitas kultural keagamaan. Artikel ini menggunakan metode penelitian kualitatif dengan mendeskripsikan amaliah keagamaan di Masjid Jami Kajen kemudian dianalisis dan diinterpretasikan. Dalam kajian ini ditemukan peran Masjid Kajen sebagai Masjid Nahdliyin yaitu: pertama, sebagai tempat ibadah shalawatan, zikir bersama dan berjabatan tangan selesai shalat; kedua, doa bersama seperti istighasah, tahlilan, yasinan, khataman Al-Quran dan shalawat barzanji; ketiga, pengkajian dan pengajian ilmu-ilmu keagamaan; keempat, melestarikan tradisi khutbah Jumat berbahasa Arab, shalat tarawih untuk dua kelompok dan ngaji kilatan; kelima, kegiatan sosial kemasyarakatan memberikan santunan kepada fakir miskin, kaum dhuafa dan yatim piatu; keenam, wadah perajut kerukunan dan ukhuwah islamiyah; ketujuh, Pusat Pelestarian Kebudayaan dengan tradisi megengan dan suronan; kedelapan, tradisi selamatan atau kenduri memperingati hari-hari besar Islam maupun suronan Kiai Ahmad Mutamakin